Assessment of Osteoporosis in Post Menopausal Women: A Clinical Study - Najam, R; Huda, N (Nepal Journal of Obstetrics and Gynaecology, 2012)
Aims: Osteoporosis is a metabolic disorder of the bones that is characterized by decreased bone density which predisposes to increased fracture risk. The disease can exist undiagnosed for a long time as it produces no distinct symptoms and is detected when a fracture has already occurred. There is sufficient evidence to state that the risk of osteoporosis and fracture increases with age and after menopause, that bone density measurements accurately predict the risk for fractures in the short-term, and that treating asymptomatic women with osteoporosis reduces their risk for fracture. The present cross sectional study was undertaken to assess osteoporosis in postmenopausal women by measuring bone mineral density (BMD). Methods: This is a prospective study, conducted at the Department of Obstetrics and Gynecology, Teerthanker Mahaveer Medical College, Moradabad. India. Post menopausal women were included in the study. Women who had undergone hysterectomy or who were on hormone replacement therapy or calcium or vitamin D preparations were excluded from the study. The participants underwent BMD measurement by Achilles Ultrasound bone densitometer. The results of BMD were analysed on the basis of T-Scores and were represented in the form of a graph. Results: Of the 90 patients that were included in the study 42.2 %( n=38) were in the age group of 45-55years. In almost 50% of patients the duration of menopause was 6-10 years. Of the 90 patients 10%(n=9)were normal, 44.4%(n=40) were osteopenic, 33.3%(n=30) were osteoporotic and 12.2%(n=11) were severely osteoporotic. Backache was the commonest presenting symptom in the study population. Conclusions: Quantitative ultrasound (QUS) is a rapid and inexpensive method of measuring bone density. In our study 90% of the postmenopausal women had subnormal T scores. We recommend regular BMD measurements in postmenopausal subjects for early diagnosis and treatment of osteoporosis in this vulnerable group. NJOG 2011 Nov-Dec; 6 (2): 11-13 DOI: http://dx.doi.org/10.3126/njog.v6i2.6749